Empowering Wana Kriya MSMEs Through Utilizing Local Wood Into Decoration and Accessory Products - Ni Putu Emilika Budi LESTARI; I Kadek PRANAJAYA; Putu Yudha Asteria PUTRI; Ni Made Emmi Nutrisia DEWI; Ni Komang PRASIANI; I Gusti Ngurah Agung Kepakisan MANDALA; Ngurah Gede Dwi MAHADIPTA; Ni Kadek Ayu Pradnya PARAMITA; Gede Dharma Arya WICAKSANA; Irfan CAHYONO; Dhanendra WIRATAMA; Ida Bagus Surya WIBAWA (PT Keberlanjutan Strategis Indonesia, 2025)
This community service program aims to empower the Wana Kriya MSME in Pering Village, Gianyar, Bali through the sustainable use of local wood to create economically valuable decorative and accessory products. The activities are carried out through several stages, including socialization, training in creativity and product design innovation, branding training, photography, product identity, and visual content. In addition, training is provided on digital marketing and social media utilization, MSME management, production, and entrepreneurship. The counseling and community empowerment program is carried out with the theme